Effects of compaction and cover crops on soil least limiting water range and air permeability - Chen, Guihua; Weil, Ray R.; Hill, Robert L. (Soil & tillage research, 2014)
•Compaction reduced soil least limiting water range (LLWR) by decreasing aeration and increasing soil strength.•The tap-rooted over crops in the Brassica increased LLWR by reducing the limitations on soil strength.•Compaction reduces soil air permeability.•Brassica cover crops increased the air permeability of compacted soils. Crop rotations that include tap-rooted species of cover crops may help alleviate the deleterious effects of soil compaction on plant growth by modifying soil physical properties. We studied the effects of compaction and cover crops on the least limiting water range (LLWR) and air permeability in the surface layers of a loamy (Exp. 1) and a sandy soil (Exp. 2). There were three compaction treatments [HC (high), MC (medium) and NC (no compaction)] and four cover crop treatments [FR (forage radish: Raphanus sativus var. longipinnatus, cultivar ‘Daikon’), rapeseed (Brassica napus, cultivar ‘Essex’), rye (cereal rye: Secale cereale L., cultivar ‘Wheeler’) and NCC (no cover crop)]. Rapeseed and FR are tap-rooted species in the Brassica family. Compaction reduced the LLWR in Exp. 1 by decreasing aeration and increasing soil strength and in Exp. 2 by increasing soil strength. Brassica cover crops increased LLWR by reducing the limitations on soil strength. Air permeability at 0–12cm depth was reduced by compaction in both experiments, and this reduction was associated with pore tortuosity and discontinuity. In Exp. 1, the air permeability under HC following various cover crop treatments was in the order of FR=rapeseed>rye=NCC; under NC condition it was in the order rapeseed=rye>FR>NCC. The overall effect of cover crops in Exp. 1 on air permeability across compaction treatments was in the order of FR=rapeseed>rye=NCC. Cover crops had no affect air permeability in Exp. 2 probably due to the coarse soil texture. The results supported our hypotheses that tap-rooted Brassica cover crops (especially rapeseed) were able to increase LLWR and air permeability, though the magnitude of the increase seemed to be less than the decrease by compaction.